Conceptual relativity and truth in the philosophy of Hilary Putnam - Villanueva González, Félix Martín (2025)
This paper analyzes the concept of conceptual relativity developed by the American philosopher Hilary Putnam, who challenges the foundations of classical realism and proposes a new way of approaching the problem of truth in science and philosophy. It emphasizes the role of language, conceptual schemes and cultural context is emphasized. The essay explores the fundamental concepts of conceptual relativity and truth. It then examines how conceptual relativity is distinguished from other philosophical positions such as metaphysical realism and cultural relativism. In addition, it examines how Putnam, inspired by classical pragmatism, redefines the notion of truth within his proposal of natural realism. The most important criticisms that other philosophers have made against Putnam´s notion of conceptual relativity are also studied. Finally, a reflection is made on the impact of these ideas on scientific knowledge, and the emphasizes the contemporary relevance of their contributions to science and philosophy.